PENINGKATAN PRODUKTIVITAS KERJA GURU MELALUI PENGEMBANGAN EFIKASI DIRI DAN KEPEMIMPINAN VISIONER - Kinanti Puji Lestari; Hendarman Hendarman; Rais Hidayat (Universitas Pakuan, 2022)
THE TEACHER’S PRODUCTIVITY ENHANCMENT BY IMPROVING SELF EFFICACY AND VISIONER LEADERSHIPThe purpose of this study was to determine the correlation between self efficacy and visionary leadership toward teacher’s productivity. The study was conducted in Vocational High School at Ciawi Region. The population of the study was 136 teachers and the sample taken was 102 teachers which were selected using proportional random sampling and data collection was got through questionnaires. The data analysing technique was done using correlation regression partial and multiple. The study result pointed out that there was positive correlation between self efficacy and teacher’s productivity (the correlation coefficient ry1 = 0,596 and the determination coefficient r2y1=0,355), there was positive correlation between visionary leadership and teacher’s productivity (the correlation coefficient ry2 =0,545 where the determination coefficient r2y2=0,297), and also there was positive correlation of self efficacy and visionary leadership to teacher’s productivity (the correlation coefficient ry12 = 0,648 and the determination coefficient r2y12= 0,419). Based on the above result study, it could be concluded that the teacher’s productivity might be improoved through self efficacy and visionary leadership either partially or concurrently.